Genomic and molecular characterisation of Escherichia marmotae from wild rodents in Qinghai-Tibet plateau as a potential pathogen - Liu, Sha (Sci Rep, 2019)
Wildlife is a reservoir of emerging infectious diseases of humans and domestic animals. Marmota himalayana mainly resides 2800–4000 m above sea level in the Qinghai-Tibetan Plateau, and is the primary animal reservoir of plague pathogen Yersinia pestis. Recently we isolated a new species, Escherichia marmotae from the faeces of M. himalayana. In this study we characterised E. marmotae by genomic analysis and in vitro virulence testing to determine its potential as a human pathogen. We sequenced the genomes of the seven E. marmotae strains and found that they contained a plasmid that carried a Shigella-like type III secretion system (T3SS) and their effectors, and shared the same O antigen gene cluster as Shigella dysenterae 8 and E. coli O38. We also showed that E. marmotae was invasive to HEp-2 cells although it was much less invasive than Shigella. Thus E. marmotae is likely to be an invasive pathogen. However, E. marmotae has a truncated IpaA invasin, and lacks the environmental response regulator VirF and the IcsA-actin based intracellular motility, rendering it far less invasive in comparison to Shigella. E. marmotae also carried a diverse set of virulence factors in addition to the T3SS, including an IS1414 encoded enterotoxin gene astA with 37 copies, E. coli virulence genes lifA/efa, cif, and epeA, and the sfp gene cluster, Yersinia T3SS effector yopJ, one Type II secretion system and two Type VI secretion systems. Therefore, E. marmotae is a potential invasive pathogen.